Activation of farnesoid X receptor suppresses ER stress and inflammation via the YY1/NCK1/PERK pathway in large yellow croaker (Larimichthys crocea) - Du, Jianlong; Zhang, Junzhi; Xiang, Xiaojun; Xu, Dan; Cui, Kun; Mai, Kangsen; Ai, Qinghui (Frontiers in Nutrition, 2022)
Unfolded protein responses from endoplasmic reticulum (ER) stress have been implicated in inflammatory signaling. The vicious cycle of ER stress and inflammation makes regulation even more difficult. This study examined effects of farnesoid X receptor (FXR) in ER-stress regulation in large yellow croakers. The soybean-oil-diet-induced expression of ER stress markers was decreased in fish with FXR activated. In croaker macrophages, FXR activation or overexpression significantly reduced inflammation and ER stress caused by tunicamycin (TM), which was exacerbated by FXR knockdown. Further investigation showed that the TM-induced phosphorylation of PERK and EIF2α was inhibited by the overexpression of croaker FXR, and it was increased by FXR knockdown. Croaker NCK1 was then confirmed to be a regulator of PERK, and its expression in macrophages is increased by FXR overexpression and decreased by FXR knockdown. The promoter activity of croaker NCK1 was inhibited by yin-yang 1 (YY1). Furthermore, the results show that croaker FXR overexpression could suppress the P65-induced promoter activity of YY1 in HEK293t cells and decrease the TM-induced expression of yy1 in macrophages. These results indicate that FXR could suppress P65-induced yy1 expression and then increase NCK1 expression, thereby inhibiting the PERK pathway. This study may benefit the understanding of ER stress regulation in fish, demonstrating that FXR can be used in large yellow croakers as an effective target for regulating ER stress and inflammation.